The Relationship Between Isbat Marriage Polygamy Sirri and Supreme Court Circular Letter (SEMA) Number 3 of. 2018 - N. Makfiyati; Syafe’i, Zakaria; Hidayat, Ahmad (Dinasti Research, 2024)
Following the issuance of SEMA Number 3 of 2018, polygamy has become a subject of considerable debate. This is due to the fact that the SEMA contains a sentence that allows for the application of isbat nikah for sirr polygamy marriages, despite the From the perspective of children's best interests, this is regarded as unacceptable by some legal practitioners and academics, who view it as contrary to the provisions of Marriage Law No. 1 of 1974 regarding marriage, as well as the prevailing Compilation of Islamic Law in Indonesia. This study aims to ascertain the position of isbat polygamy sirr in relation to the Marriage Law and the Compilation of Islamic Law, taking into account the provisions of SEMA Number 03 of 2018. Adopting a qualitative research approach with a normative legal perspective, the study draws primarily on library research, employing both a legal approach and a conceptual approach to data collection. Following an exhaustive investigation and deliberation, it can be concluded that the SEMA has effectively barred the possibility of obtaining an isbat nikah for polygamy sirr. The 3/2018 decree must be re-examined, particularly with regard to the relevance and suitability of the principles of benefit pertaining to women who are adversely affected by this action. The prohibition of this SEMA does not imply that the polygamous marriage in question is considered invalid. This is because the context of this SEMA solely pertains to the authority of judges. It can be interpreted that this SEMA acknowledges the religious validity of the marriage, thereby recognizing the legitimacy of the children produced from this union. The issuance of this SEMA, however, is a misstep as it has a detrimental impact on women in polygamous relationships.